2012
DOI: 10.1039/c1ob06536j
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of uracil nucleosides with intrinsic fluorescence (NIF-analogues): synthesis and photophysical properties

Abstract: Uridine cannot be utilized as fluorescent probe due to its extremely low quantum yield. For improving the uracil fluorescence characteristics we extended the natural chromophore at the C5 position by coupling substituted aromatic rings directly or via an alkenyl or alkynyl linker to create fluorophores. Extension of the uracil base was achieved by treating 5-I-uridine with the appropriate boronic acid under the Suzuki coupling conditions. Analogues containing an alkynyl linker were obtained from 5-I-uridine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…The survey of reaction conditions showed that existing solution‐phase halouridine Suzuki‐Miyaura cross‐coupling reaction methods,,,,, are not suitable for use in solid‐phase synthesis of C‐5 uridine derivatives due to several limitations: i ) harsh reaction conditions ‐ reactions are carried out in the presence of strong alkaline solution (KOH) and currently available solid‐support linkage will not survive under coupling conditions; ii ) long reaction time (e. g. 24–48 h); iii ) elevated reaction temperature (∼200 °C); iv ) use of phosphine ligands, v ) poor yields and vi ) tedious purification processes . There is an urgent need to develop mild and practical reaction conditions for Suzuki‐Miyaura cross coupling of 5‐iodouridine with aryl/heteroaryl boronic acids, which can be transferable to solid‐phase organic synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The survey of reaction conditions showed that existing solution‐phase halouridine Suzuki‐Miyaura cross‐coupling reaction methods,,,,, are not suitable for use in solid‐phase synthesis of C‐5 uridine derivatives due to several limitations: i ) harsh reaction conditions ‐ reactions are carried out in the presence of strong alkaline solution (KOH) and currently available solid‐support linkage will not survive under coupling conditions; ii ) long reaction time (e. g. 24–48 h); iii ) elevated reaction temperature (∼200 °C); iv ) use of phosphine ligands, v ) poor yields and vi ) tedious purification processes . There is an urgent need to develop mild and practical reaction conditions for Suzuki‐Miyaura cross coupling of 5‐iodouridine with aryl/heteroaryl boronic acids, which can be transferable to solid‐phase organic synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Evaporation of the solvent gave the crude product, which was purified by column chromatography over silica gel, yielding 364 mg (55%) of a white solid. Mp: >218°C dec. 1 5-Nitro-2′-deoxyuridine-3′,5′-O-diacetate (15). 2′-Deoxyuridine, 14 (5 g, 0.02 mol), was treated with acetic anhydride (11 μL, 0.12 mol) in pyridine (200 mL) at room temperature overnight.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Therefore synthesis of unnatural nucleosides arises continuous interest because of their wide biological potential. For instance, 5-substituted 2'-deoxyuridines have been reported as efficient candidates in DNA labeling, modification, and other studies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], and they also exhibit significant antiviral [ 18 , 19 , 20 , 21 , 22 , 23 ], antibacterial [ 24 ], and anticancer activities [ 25 , 26 , 27 ]. Due to the importance of modified nucleosides, all major classes of palladium-catalyzed reactions have been extensively developed to introduce various substituents [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…However protection/deprotection sequences induce generally a loss of material and increase the waste production. Recently, Suzuki-Miyaura reactions on unprotected 2'-deoxyuridines in an aqueous-organic solvent system were described, where tetrahydrofuran, acetonitrile, methanol or dimethylformamide was used as co-solvent [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 39 , 40 ]. To the best of our knowledge, only two examples in the 5-iodouridine [ 41 , 42 ] and one in the 2'-deoxy-uridine [ 43 ] series are reported in the literature where the experimental conditions required either tris(3-sulfonatophenyl)phosphine trisodium salt (TPPTS) as a specific ligand or palladium supported on reverse phase glass beads.…”
Section: Introductionmentioning
confidence: 99%